Premature death in adults with 22q11.2 deletion syndrome. Issue 5 (25th February 2009) - Bassett, A S; Chow, E W C; Husted, J; Hodgkinson, K A; Oechslin, E; Harris, L; Silversides, C
Abstract : Background: 22q11.2 deletion syndrome (22q11.2DS) is a multisystem disease with a prevalence of 1/4000. Variable expression of congenital and later onset features contributes to its under-recognition. Longevity in those surviving childhood is believed to be normal but data are limited. Methods: We prospectively followed 264 subjects; 102 adults (>17 years) with 22q11.2DS (44 male (M), 58 female (F); mean (SD) age 33.6 (10.9) years) and their 162 unaffected siblings (77 M, 85 F; mean age 36.1 (12.2) years). We compared survival between groups using Kaplan–Meier estimates. Results: Twelve (11.8%; 4 M, 8 F) individuals with 22q11.2DS and no siblings died (p<0.0001). Survival to ages 40 and 50 years was 89.9% and 73.9%, respectively. Median age at death was 41.5 (range 18.1–68.6) years. Deaths included two (7.7%) of 26 subjects with neither major congenital heart disease (CHD) nor schizophrenia. Four of six sudden and unexpected deaths occurred in individuals with no major CHD. There was no evidence of cancer or coronary artery disease or family history of sudden death in the 12 patients who died, six of whom had autopsies. Discussion: Individuals with 22q11.2DS who survive childhood have diminished life expectancy and increased risk of sudden death not attributable to any single factor. Some sudden and/or premature deaths observed in the general population may represent undiagnosed 22q11.2DS. Increased recognition of the syndrome by family doctors, specialists and coroners will be essential to facilitate the tissue studies needed to determine underlying mechanisms.